Current status and prospect of transcutaneous auricular vagus nerve stimulation for disorders of consciousness - Wang, Yifei; Zhang, Jinling; Zhai, Weihang; Wang, Yu; Li, Shaoyuan; Yang, Yi; Zheng, Yanfeng; He, Jianghong; Rong, Peijing (Frontiers in Neuroscience, 2024)
Disordered Consciousness (DOC) is among neurological disorders for which there is currently no admitted treatment. The pathogenesis of DOC is still unclear, covering a variety of indistinguishable types of diseases, high misdiagnosis rate and poor prognosis. Most treatments remain to be clarified in the future to provide adequate evidence for clinical guidance. Neuromodulation technology aims to regulate neural circuits to promote awakening more directly. At present, it is confirmed that the potential of transcutaneous auricular vagus nerve stimulation (taVNS) as a therapeutic tool is worth exploring in the context of consciousness disorders, as previously proposed for invasive forms of VNS, in which the means of stimulating the vagus nerve to change the brain areas related to cosciousness have also received widespread attention. In this paper, we review the literature on taVNS and DOC to better understand the current status and development prospect of taVNS treament as a non-invasive neuromodulation method with sensitivity and/or specificity at the single subject.